Pengaruh Iklan terhadap Citra Merek Konsumen KFC Ciracas Jakarta Timur - Uzlifatul Hasanah; Novie Kurniasih (Jurnal Utilitas, 2018)
This research aims to determine the effect of advertising to Brand Image on KFC Ciracas consumers, East Jakarta. The research used an associative quantitative research method. The population in this research were 5618 consumers. The sampling technique used was incidental sampling and the sample determined in this study amounted to 98 respondents using the Slovin formula. After the data are known to have the same characteristics and normal distribution based on the normality test, followed by analysis of variance (ANAVA). Based on the results of linear regression calculations obtained Ŷ = 19.91 + 0.67 (x) and the results of ANAVA calculations obtained Fcount < Ftable (0.655 < 1,63). The hypothesis testing was done by Pearson’s product moment correlation and obtained rxy= 0.606, which showed that there is a strong influence of advertising on Brand Image and in accordance with the interpretation criteria in the correlation coefficient interpretation table that is 0,600 - 0,799. Therefore, the study concluded that there was the effect of advertising to Brand Image on consumers of KFC Ciracas, East Jakarta. Keywords: Advertising, Brand Image, Quantitative Associative Research